2009
DOI: 10.5424/sjar/2009073-450
|View full text |Cite
|
Sign up to set email alerts
|

Within-plant distribution and seasonal population dynamics of flower thrips (Thysanoptera: Thripidae) infesting French beans (Phaseolus vulgaris L.) in Kenya

Abstract: The aim of this research was to study spatial distribution of flower thrips on French beans (Phaseolus vulgaris L.) in Kenya. Their build up and seasonal population dynamics was monitored using sticky blue colour traps and sampling of leaves and flowers in two seasons in 2002. Thrips infested French beans from the second week after crop emergence. Their population peaked at peak flowering. The sticky trap catches were linearly related to the actual presence of thrips on the crop and could estimate population b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 10 publications
2
10
0
2
Order By: Relevance
“…1B, 2B, 3B), depending on genotype, which coincided with the peak of flowering in all the cultivars. Several authors had observed such trends in flower thrips population under natural infestation in Kenya (Kasina et al, 2009;Nyasani et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…1B, 2B, 3B), depending on genotype, which coincided with the peak of flowering in all the cultivars. Several authors had observed such trends in flower thrips population under natural infestation in Kenya (Kasina et al, 2009;Nyasani et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Bean fly damage may result in seedling death under severe infestation (Abate and Ampofo, 1996). In contrast, flower thrips start infesting at the vegetative stage and migrate later into flower buds and flowers (Kasina et al, 2009). Thrips infestation levels were higher in snap beans planted in the first dry season (January 2002) than in the second dry season (July 2002) in MweaTebere (Kasina et al 2009).…”
Section: Introductionmentioning
confidence: 94%
“…In contrast, flower thrips start infesting at the vegetative stage and migrate later into flower buds and flowers (Kasina et al, 2009). Thrips infestation levels were higher in snap beans planted in the first dry season (January 2002) than in the second dry season (July 2002) in MweaTebere (Kasina et al 2009). Damage by flower thrips results in premature fall of flower buds and flowers.…”
Section: Introductionmentioning
confidence: 99%
“…Igualmente, se presentaron diferencias significativas en la comparación entre los promedios de la densidad poblacional del trips de acuerdo a su estado de desarrollo de ninfa y adulto con cada estructura, lo que evidenció que tanto adultos como ninfas del insecto también se encuentran en mayor numero en los terminales. Algunos trabajos realizados sobre trips registran que la mayor incidencia de este insecto se observa cuando la planta llega o está en periodo de floración (Ávila Quezada et al, 2002;Urías-López et al, 2007;Kasina et al, 2009). Sin embargo, estos estudios no describen en que parte de la planta el insecto se ubicó después de que hizo su aparición.…”
Section: Resultados Y Discusiónunclassified